PENGGUNAAN METODE JEROME BRUNER UNTUK MEREMEDIASI MISKONSEPSI PESERTA DIDIK SMP PADA MATERI HUKUM ARCHIMEDES - Kristin Mery Handayani; Edy Tandililing; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims is to be aware the remediation of student’s misconceptions by using Jerome Bruner’s learning  method on Archimedes principle at SMP Negeri 23 Pontianak. the pre-experimental design with one group pre-test-post-test design was used in this research. The sample of this research is students of class VIII F (n = 30 student) which are chosen by random sampling technique of an intact group. The instruments in this research were diagnostic tests consisting of 15 pre-test question and 15 multiple choice post-test questions with open reasons.  Based on data analysis, the  findings are : (1) The percentage reduction of students who misconceptions, after remediation  on indicator I  of  82%;  indicator II of  65%; and indicator III of  72%, with an average of  73%.  (2) There is a significant conceptual change with Mc Nemar statistic test (χ2calculate   for the whole indicator that is equal to 34,58; dk = 1 ; ∝ =0,05) after remediation. (3) The effect size of  1,75 (high category). Based on these results It was expected that Jerome Bruner’s learning  method can be used as an alternative remediation learning  activity to reduce misconceptions.  Keywords:   Misconception, Remediation, Jerome Bruner’s Learning Method, Archimedes  Principle